DAMPAK PENERAPAN ARTIFICIAL INTELLIGENCE PADA IKLAN DIGITAL PRODUK KESEHATAN BLACK MORES TERHADAP BRAND AWARENESS - Efry Kurnia; Roza Maya Sari; Novi Aisha (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2026)
Public demand and desire for rapid, reliable information are growing alongside continuous technological advancements—specifically the use of AI technologies that deliver quick and practical results in the business world, including the health product sector. Blackmores is a well-known health product brand, particularly in Asia; however, there is a perceived need for its products to be presented through more communicative, personalized messaging. This study aims to analyze the impact of AI implementation in Blackmores health product advertisements on consumer brand awareness in Indonesia. Data was collected via an online questionnaire involving 200 respondents who had encountered the advertisements on various social media platforms.